A method for preparing nitrogen-bismuth co-doped porous graphite felt, graphite felt prepared thereby, and application thereof

The preparation of nitrogen and bismuth co-doped porous graphite felts through solution jet spinning process, which solved the problems of poor mechanical properties and easy corrosion of carbon electrode materials, and significantly improved the energy efficiency and stability of all-vanadium redox flow batteries.

CN118970074BActive Publication Date: 2025-02-25ZHEJIANG XINGHUI NEW MATERIALS TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411448762.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-25
Estimated Expiration
2044-10-17

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention provides a method for preparing nitrogen-bismuth co-doped porous graphite felt, as well as the graphite felt obtained therefrom and its applications, relating to the field of vanadium redox flow battery technology. The preparation method includes the following steps: needle-punching polyacrylonitrile-based carbon fibers to obtain PAN-based carbon fiber soft felt; dissolving polyacrylonitrile, urea, and bismuth salt in a solvent to obtain a precursor solution; spraying the precursor solution onto the PAN-based carbon fiber soft felt using a solution jet spinning process, followed by drying to obtain a spinning substrate; and sequentially pre-carbonizing, carbonizing, and graphitizing the spinning substrate to obtain the nitrogen-bismuth co-doped porous graphite felt. The porous graphite felt structure of this invention can significantly increase the specific surface area of ​​the graphite felt, improve and enhance hydrophilicity, increase the conductivity of the graphite felt, and increase surface functional groups, which is beneficial for improving the efficiency of vanadium redox flow batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of all-vanadium redox flow batteries, and in particular to a method for preparing nitrogen-bismuth co-doped porous graphite felt, the graphite felt prepared thereby, and applications thereof. Background Art

[0002] All-vanadium redox flow battery (VRFB) has the advantages of high power, long life, deep discharge, high efficiency, etc. It is the only energy storage method that can match the long service life of wind power and photovoltaic products. After years of development, it is in the early stage of industrial application. As one of the key components of VRFB, the performance of electrode material has a great impact on the battery.

[0003] Non-metallic electrode materials such as carbon electrodes have attracted extensive attention and research from researchers due to their good conductivity and wide electrochemical window, as well as their ability to exist stably in sulfuric acid media. Traditional carbon electrodes mainly include glassy carbon, carbon paper, carbon cloth, carbon felt, graphite felt, etc. However, due to the limitations of electrode reaction kinetics, the electrochemical activity of these materials is not ideal.

[0004] When traditional carbon materials are used as electrodes, especially positive electrode materials, they have poor mechanical properties and will be severely corroded, powdered or etched during long-term use, leading to battery failure, which limits their application in VRFB. Therefore, it is necessary to improve the electrochemical activity of electrode felt to improve its application in VRFB.

[0005] CN 118213549 A discloses a method of immersing graphite felt in a urea aqueous solution and calcining it to obtain N-doped graphite felt, using the N-doped graphite felt as a substrate, and electro-depositing Bi on its surface to obtain N-Bi-doped graphite felt. CN116314856A discloses a method of in-situ loading ZIF-8 on a graphite felt substrate and carbonizing it, and then using its microporous structure to absorb Bi through liquid phase impregnation. 3+ , and the N atoms therein are used for anchoring Bi atoms to form Bi-N bonds during the later high-temperature calcination, so that the Bi single atoms are evenly and stably dispersed on the carbon substrate sintered by ZIF-8, thereby preparing a single-atom catalyst composite electrode graphite felt with high catalytic activity and high stability. CN118507755A discloses a method of utilizing an electrostatic spinning process, using a carbon fiber material as a substrate, collecting the spinning on a drum receiver, and performing pre-carbonization and high-temperature carbonization treatment to achieve N-doped oriented carbon fibers. However, the above method has the disadvantages of being cumbersome, time-consuming, having safety risks in the use of high voltage electricity, and having low production efficiency; and the stability and durability of the battery operation improved by the hydrogen evolution reaction need to be further improved.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing nitrogen-bismuth co-doped porous graphite felt, and the graphite felt prepared thereby and its application. The present invention proposes a method of using solution jet spinning to use PAN-based carbon fiber soft felt as a substrate, collect the spinning on a drum receiver and perform pre-carbonization and high-temperature carbonization treatment, and then obtain nitrogen-bismuth co-doped porous active graphite felt by high-temperature graphitization. This method can not only construct a porous structure for the electrode felt and introduce heteroatoms to increase its specific surface area and active sites, but also inhibit the hydrogen evolution reaction to improve the stability and durability of the battery operation, save energy and time, and to a certain extent reduce the investment cost of VRFB.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] In a first aspect, the present invention provides a method for preparing nitrogen-bismuth co-doped porous graphite felt, the preparation method comprising the following steps:

[0010] The polyacrylonitrile-based carbon fiber is needle-punched to obtain a PAN-based carbon fiber soft felt;

[0011] dissolving polyacrylonitrile, urea and bismuth salt in a solvent to obtain a precursor solution;

[0012] The precursor solution is sprayed onto the PAN-based carbon fiber soft felt by a solution jet spinning process, and then dried to obtain a spinning base;

[0013] The spinning substrate is sequentially subjected to pre-carbonization treatment, carbonization treatment and graphitization treatment to obtain the nitrogen-bismuth co-doped porous graphite felt.

[0014] Preferably, the average diameter of the polyacrylonitrile-based carbon fiber is 5-10 μm.

[0015] Preferably, the average length of the polyacrylonitrile-based carbon fiber is 50-100 mm.

[0016] Preferably, the density of the acupuncture treatment is 1 to 10 needles / cm.

[0017] Preferably, the density of the PAN-based carbon fiber soft felt is 0.6-1.0 g / cm 3 .

[0018] Preferably, the thickness of the PAN-based carbon fiber soft felt is 2-6 mm.

[0019] Preferably, the precursor solution is composed of the following components in percentage by mass: 8-14% polyacrylonitrile, 3-10% urea, 2-8% bismuth salt, and the remainder is solvent.

[0020] Preferably, the number average molecular weight of the polyacrylonitrile is 80,000-150,000.

[0021] Preferably, the bismuth salt is selected from bismuth chloride and / or bismuth nitrate.

[0022] Preferably, the solvent is selected from N,N -Dimethylformamide.

[0023] Preferably, the dissolving temperature is 60-80°C.

[0024] Preferably, the dissolving is carried out under stirring conditions, and the stirring speed is 200-400 rpm.

[0025] Preferably, the dissolving is carried out under stirring conditions, and the stirring time is 20 to 200 min.

[0026] Preferably, the spinning substrate is prepared by the following steps:

[0027] The PAN-based carbon fiber soft felt is placed on a receiving curtain, and a solution jet spinning device is turned on to spray the precursor solution onto the PAN-based carbon fiber soft felt. The spun substrate is collected and dried to obtain the spinning substrate.

[0028] Preferably, the parameters of the solution jet spinning process include the following conditions:

[0029] The propulsion speed of the syringe is 0.3~3.0 mL / min, the air pressure is 0.2~1.0 MPa, the distance between the spinneret and the receiving plate is 30~70 cm; the ambient temperature is 20~40℃, and the ambient humidity is 20~50%; the spinning time is 5~10 h.

[0030] Preferably, during the preparation of the spinning substrate, the drying temperature is 25-100°C.

[0031] Preferably, during the preparation of the spinning substrate, the drying time is 1 to 4 hours.

[0032] Preferably, the temperature of the pre-carbonization treatment is 220-300°C.

[0033] Preferably, the pre-carbonization treatment time is 1 to 3 h.

[0034] Preferably, the heating rate of the pre-carbonization treatment is 5°C / min or less.

[0035] Preferably, the carbonization treatment is performed in the presence of a protective gas.

[0036] Preferably, the protective gas comprises nitrogen and / or argon.

[0037] Preferably, the flow rate of the protective gas is above 5 mL / min.

[0038] Preferably, the temperature of the carbonization treatment is 800-1200°C.

[0039] Preferably, the carbonization treatment time is 1 to 3 h.

[0040] Preferably, the heating rate of the carbonization treatment is below 5°C / min.

[0041] Preferably, the graphitization treatment is performed in the presence of a protective gas.

[0042] Preferably, the protective gas comprises nitrogen and / or argon.

[0043] Preferably, the ventilation rate of the protective gas is 300-500 m / s. 3 / h.

[0044] Preferably, the graphitization treatment procedure is: firstly heating to 800-1200°C and maintaining for 0.5-10 h, and then heating to 2000-3000°C and maintaining for 0.5 h-10 h.

[0045] Preferably, the heating rate of the graphitization treatment is 5-10°C / min.

[0046] In a second aspect, the present invention provides a nitrogen-bismuth co-doped porous graphite felt, wherein the nitrogen-bismuth co-doped porous graphite felt is prepared by the preparation method of the nitrogen-bismuth co-doped porous graphite felt as described in the first aspect.

[0047] In a third aspect, the present invention provides a use of the nitrogen-bismuth co-doped porous graphite felt as described in the second aspect in the preparation of an all-vanadium liquid flow battery electrode.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] (1) The present invention uses PAN-based carbon fiber soft felt as a substrate and is composited with a liquid-jet spun carbon fiber membrane. The liquid-jet spun carbon fiber membrane is prepared by solution jet spinning and carbonization of PAN and has a nanoscale pore structure; the pore size on the surface of the carbon felt is about 60 to 200 nm, and the specific surface area is significantly increased, which is conducive to providing more active sites for redox reactions.

[0050] (2) The present invention adopts a solution jet spinning process, which has a simple and easy-to-operate preparation process, strong controllability, a wide range of applications, can prepare nanofiber membranes on a large scale, has adjustable fiber morphology, and a wide range of material applications. Compared with electrospinning, the solution jet spinning process is easier to achieve large-scale production, has high production efficiency, and can also avoid the risk of electric shock during the use of high-voltage equipment.

[0051] (3) After the nitrogen-bismuth co-doped porous active graphite felt provided by the present invention is used as an electrode, the sum of the activation loss and concentration polarization loss of the battery is reduced by 65-70%; the hydrogen evolution current is reduced by 40-60%; the energy efficiency of VRFB is as high as 320 mA / cm 2 The voltage efficiency and energy efficiency showed no obvious signs of degradation over 500 cycles, indicating that the electrode provided by the present invention has excellent stability and durability in single cell tests. DETAILED DESCRIPTION

[0052] Unless otherwise defined herein, scientific and technological terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0053] It should be noted that specific details are described in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0054] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] In a first aspect, the present invention provides a method for preparing nitrogen-bismuth co-doped porous graphite felt, the preparation method comprising the following steps:

[0056] The polyacrylonitrile-based carbon fiber is needle-punched to obtain a PAN-based carbon fiber soft felt;

[0057] dissolving polyacrylonitrile, urea and bismuth salt in a solvent to obtain a precursor solution;

[0058] The precursor solution is sprayed onto the PAN-based carbon fiber soft felt by a solution jet spinning process, and then dried to obtain a spinning base;

[0059] The spinning substrate is sequentially subjected to pre-carbonization treatment, carbonization treatment and graphitization treatment to obtain the nitrogen-bismuth co-doped porous graphite felt.

[0060] In the present invention, the invention uses the PAN-based carbon fiber soft felt obtained by needle punching as the substrate and is composited with the liquid-sprayed carbon fiber membrane. The obtained carbon felt has a nanoscale pore structure and the specific surface area is significantly improved, which is conducive to providing more active sites for redox reactions. After the nitrogen-bismuth co-doped porous active graphite felt of the present invention is used as an electrode, the activation loss and concentration polarization loss of the battery can be significantly reduced, the energy efficiency of VRFB can be significantly improved, and the prepared nitrogen-bismuth co-doped porous graphite felt shows excellent stability and durability in single cell tests.

[0061] As an optional embodiment, the average diameter of the polyacrylonitrile-based carbon fiber is 5-10 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc.

[0062] As an optional embodiment, the average length of the polyacrylonitrile-based carbon fiber is 50-100 mm, for example, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, 100 mm, etc.

[0063] As an optional embodiment, the density of the acupuncture treatment is 1 to 10 needles / cm 2 , for example, 1 needle / cm 2 , 2 needles / cm 2 , 3 needles / cm 2 , 4 needles / cm 2 , 5 needles / cm 2 , 6 needles / cm 2 , 7 needles / cm 2 , 8 needles / cm 2 , 9 needles / cm 2 , 10 needles / cm 2 wait.

[0064] As an optional embodiment, the density of the PAN-based carbon fiber soft felt is 0.6-1.0 g / cm 3 , for example, it can be 0.6 g / cm 3 , 0.7 g / cm 3 , 0.8 g / cm 3 , 0.9 g / cm 3 , 1.0 g / cm 3 wait.

[0065] As an optional embodiment, the thickness of the PAN-based carbon fiber soft felt is 2-6 mm, for example, it can be 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, 5.5 mm, 6 mm, etc.

[0066] As an optional embodiment, the precursor solution is composed of the following components in percentage by mass: 8-14% polyacrylonitrile, 3-10% urea, 2-8% bismuth salt, and the remainder is solvent.

[0067] As an optional embodiment, taking the total mass of the precursor solution as 100%, the content of polyacrylonitrile in the precursor solution is 8-14%, for example, it can be 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, etc.

[0068] As an optional embodiment, taking the total mass of the precursor solution as 100%, the content of urea in the precursor solution is 3-10%, for example, it can be 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, etc.

[0069] As an optional embodiment, the number average molecular weight of the polyacrylonitrile is 80,000-150,000, for example, 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000, 150,000, etc.

[0070] As an optional embodiment, the bismuth salt is selected from bismuth chloride and / or bismuth nitrate.

[0071] As an optional embodiment, the solvent is selected from N,N -Dimethylformamide.

[0072] As an optional embodiment, the dissolution temperature is 60-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, etc.

[0073] As an optional embodiment, the dissolution is carried out under stirring conditions, and the stirring speed is 200-400 rpm, for example, it can be 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, etc.

[0074] As an optional embodiment, the dissolution is carried out under stirring conditions, and the stirring time is 20 to 200 min, for example, it can be 20 min, 40 min, 60 min, 80 min, 100 min, 120 min, 140 min, 160 min, 180 min, 200 min, etc.

[0075] As an optional embodiment, the spinning substrate is specifically prepared by the following steps:

[0076] The PAN-based carbon fiber soft felt is placed on a receiving curtain, and a solution jet spinning device is turned on to spray the precursor solution onto the PAN-based carbon fiber soft felt. The spun substrate is collected and dried to obtain the spinning substrate.

[0077] As an optional embodiment, the parameters of the solution jet spinning process include the following conditions:

[0078] The propulsion speed of the syringe is 0.3~3.0 mL / min, the air pressure is 0.2~1.0 MPa, the distance between the spinneret and the receiving plate is 30~70 cm; the ambient temperature is 20~40℃, and the ambient humidity is 20~50%; the spinning time is 5~10 h.

[0079] As an optional embodiment, during the solution jet spinning process, the propulsion speed of the syringe is 0.3~3.0 mL / min, for example, it can be 0.3 mL / min, 0.5 mL / min, 0.6 mL / min, 0.8 mL / min, 1.0 mL / min, 1.2 mL / min, 1.4 mL / min, 1.6 mL / min, 1.8 mL / min, 2.0 mL / min, 2.4 mL / min, 2.6 mL / min, 2.8 mL / min, 3.0 mL / min, etc.

[0080] As an optional embodiment, during the solution jet spinning process, the air pressure is 0.2~1.0 MPa, for example, it can be 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1.0 MPa, etc.

[0081] As an optional embodiment, during the solution jet spinning process, the distance between the spinneret and the receiving plate is 30 to 70 cm, for example, it can be 30 cm, 35 cm, 40 cm, 45 cm, 50 cm, 55 cm, 60 cm, 65 cm, 70 cm, etc.

[0082] As an optional embodiment, during the solution jet spinning process, the ambient temperature is 20-40°C, for example, 20°C, 25°C, 30°C, 35°C, 40°C, etc.

[0083] As an optional embodiment, during the solution jet spinning process, the ambient humidity is 20-50%, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.

[0084] As an optional embodiment, during the solution jet spinning process, the spinning time is 5 to 10 h, for example, it can be 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h, 10 h, etc.

[0085] As an optional embodiment, during the preparation of the spinning substrate, the drying temperature is 25~100℃, for example, it can be 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, etc.

[0086] As an optional embodiment, during the preparation of the spinning substrate, the drying time is 1 to 4 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, etc.

[0087] As an optional embodiment, the temperature of the pre-carbonization treatment is 220~300℃, for example, it can be 220℃, 225℃, 230℃, 235℃, 240℃, 245℃, 250℃, 255℃, 260℃, 265℃, 270℃, 275℃, 280℃, 285℃, 290℃, 295℃, 300℃, etc.

[0088] As an optional embodiment, the pre-carbonization treatment time is 1 to 3 h, for example, it can be 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3 h, etc.

[0089] As an optional embodiment, the heating rate of the pre-carbonization treatment is below 5°C / min, for example, it can be 5°C / min, 4.5°C / min, 4°C / min, 3.5°C / min, 3°C / min, 2.5°C / min, 2°C / min, 1.5°C / min, 1°C / min, 0.5°C / min, 0.2°C / min, 0.1°C / min, etc.

[0090] As an optional embodiment, the carbonization treatment is performed in the presence of a protective gas.

[0091] As an optional embodiment, in the carbonization process, the protective gas includes nitrogen and / or argon.

[0092] As an optional embodiment, in the carbonization treatment, the flow rate of the protective gas is above 5 mL / min, for example, it can be 5 mL / min, 5.5 mL / min, 6 mL / min, 6.5 mL / min, 7 mL / min, 7.5 mL / min, 8 mL / min, 8.5 mL / min, 9 mL / min, 9.5 mL / min, 10 mL / min, etc.

[0093] As an optional embodiment, the temperature of the carbonization treatment is 800-1200°C, for example, it can be 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, etc.

[0094] As an optional embodiment, the carbonization treatment time is 1 to 3 h, for example, it can be 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3 h, etc.

[0095] As an optional embodiment, the heating rate of the carbonization treatment is below 5°C / min, for example, it can be 5°C / min, 4.5°C / min, 4°C / min, 3.5°C / min, 3°C / min, 2.5°C / min, 2°C / min, 1.5°C / min, 1°C / min, 0.5°C / min, 0.2°C / min, 0.1°C / min, etc.

[0096] As an optional embodiment, the graphitization treatment is performed in the presence of a protective gas.

[0097] As an optional embodiment, in the graphitization process, the protective gas includes nitrogen and / or argon.

[0098] As an optional embodiment, during the graphitization treatment, the ventilation rate of the protective gas is 300-500 m / s. 3 / h, for example, 300 m 3 / h, 320 m 3 / h, 340 m 3 / h、350 m 3 / h, 360 m 3 / h、380 m 3 / h、400 m 3 / h, 420 m 3 / h, 440 m 3 / h, 450 m 3 / h, 460 m 3 / h, 480 m 3 / h、500 m 3 / h, etc.

[0099] As an optional implementation, the graphitization treatment procedure is: firstly heat up to 800-1200°C and keep for 0.5-10 h, then heat up to 2000-3000°C and keep for 0.5 h-10 h.

[0100] As an optional embodiment, during the graphitization treatment, the graphitization temperature of the first stage is 800-1200°C, for example, it can be 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, etc.

[0101] As an optional embodiment, during the graphitization treatment, the time of the graphitization in the first stage is 0.5 to 10 h, for example, it can be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, etc.

[0102] As an optional embodiment, during the graphitization treatment, the graphitization temperature of the second stage is 2000~3000℃, for example, it can be 2000℃, 2100℃, 2200℃, 2300℃, 2400℃, 2500℃, 2600℃, 2700℃, 2800℃, 2900℃, 3000℃, etc.

[0103] As an optional embodiment, during the graphitization treatment, the time of the second stage graphitization is 0.5 to 10 h, for example, 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, etc.

[0104] As an optional embodiment, the heating rate of the graphitization treatment is 5~10℃ / min, for example, it can be 5℃ / min, 5.5℃ / min, 6℃ / min, 6.5℃ / min, 7℃ / min, 7.5℃ / min, 8℃ / min, 8.5℃ / min, 9℃ / min, 9.5℃ / min, 10℃ / min, etc.

[0105] In a second aspect, the present invention provides a nitrogen-bismuth co-doped porous graphite felt, wherein the nitrogen-bismuth co-doped porous graphite felt is prepared by the preparation method of the nitrogen-bismuth co-doped porous graphite felt as described in the first aspect.

[0106] In a third aspect, the present invention provides a use of the nitrogen-bismuth co-doped porous graphite felt as described in the second aspect in the preparation of an all-vanadium liquid flow battery electrode.

[0107] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0108] Example 1

[0109] This embodiment provides a nitrogen-bismuth co-doped porous graphite felt, and the nitrogen-bismuth co-doped porous graphite felt is prepared by the following steps:

[0110] S1. Preparation of PAN-based carbon fiber soft felt:

[0111] The polyacrylonitrile-based carbon fibers with an average diameter of 6 μm and an average length of 70 mm were needle-punched at a density of 2 needles / cm 2 , obtain PAN-based carbon fiber soft felt; wherein the density of the PAN-based carbon fiber soft felt is 0.8g / cm 3 , thickness is 2.5 mm.

[0112] S2. Jet spinning to prepare spinning substrate:

[0113] (S2-1) 8% polyacrylonitrile (number average molecular weight 10,000), 3% urea and 2% BiCl3 were dissolved in DMF under stirring (200 rpm), heated to 70 °C and stirred for 60 min to form a uniform precursor solution;

[0114] (S2-2) using a solution jet spinning process, injecting a precursor solution into a syringe, placing the PAN-based carbon fiber soft felt obtained in S1 on a receiving curtain, turning on a solution jet spinning device, spraying the precursor solution onto the PAN-based carbon fiber soft felt, collecting the spun fibers on the receiving curtain and drying them, and obtaining the spinning substrate;

[0115] The propulsion speed of the syringe is 0.3 mL / min, the air pressure is 0.3 MPa, the distance between the spinneret and the receiving mesh curtain is 40 cm, the ambient temperature is 25°C, the humidity is 30%, and the spinning time is 8 h; the drying is to dry the material in a vacuum drying oven at 40°C for 8 h.

[0116] S3. Preparation of Nitrogen-Bi Co-doped Porous Graphite Felt:

[0117] (S3-1) The spinning substrate obtained in S2 was placed in a muffle furnace for pre-carbonization at 200°C for 2 h with a heating rate of 3°C / min;

[0118] (S3-2) The pre-carbonized felt obtained in S3-1 was carbonized in a tubular furnace at 1000°C for 2 h under a N2 atmosphere, with a heating rate of 5°C / min and a N2 flow rate of 5 mL / min;

[0119] (S3-3) The carbonized felt obtained in S3-2 was graphitized in a tubular furnace. In a N2 atmosphere, the temperature was first raised to 800°C at a rate of 5°C / min and maintained for 1 h, and then raised to 2000°C at a rate of 5°C / min and maintained for 3 h. The ventilation rate of the protective gas was 300 m / s. 3 / h, to obtain the nitrogen-bismuth co-doped porous graphite felt.

[0120] Example 2

[0121] This embodiment provides a nitrogen-bismuth co-doped porous graphite felt, and the nitrogen-bismuth co-doped porous graphite felt is prepared by the following steps:

[0122] S1. Preparation of PAN-based carbon fiber soft felt:

[0123] The polyacrylonitrile-based carbon fibers with an average diameter of 7 μm and an average length of 70 mm were needle-punched at a density of 3 needles / cm 2 , obtain PAN-based carbon fiber soft felt; wherein the density of the PAN-based carbon fiber soft felt is 1.0 g / cm 3 , thickness is 3 mm.

[0124] S2. Jet spinning to prepare spinning substrate:

[0125] (S2-1) 10% polyacrylonitrile (number average molecular weight 10,000), 5% urea and 3% BiCl3 were dissolved in DMF under stirring (400 rpm), heated to 70 °C and stirred for 60 min to form a uniform precursor solution;

[0126] (S2-2) using a solution jet spinning process, injecting a precursor solution into a syringe, placing the PAN-based carbon fiber soft felt obtained in S1 on a receiving curtain, turning on a solution jet spinning device, spraying the precursor solution onto the PAN-based carbon fiber soft felt, collecting the spun fibers on the receiving curtain and drying them, and obtaining the spinning substrate;

[0127] The syringe advancement speed is 0.5 mL / min, the air pressure is 0.5 MPa, the distance between the spinneret and the receiving mesh curtain is 50 cm, the ambient temperature is 35°C, the humidity is 40%, and the spinning time is 10 h; the drying is to dry the material in a vacuum drying oven at 40°C for 8 h.

[0128] S3. Preparation of Nitrogen-Bi Co-doped Porous Graphite Felt:

[0129] (S3-1) The spinning substrate obtained in S2 was placed in a muffle furnace for pre-carbonization at 300°C for 3 h with a heating rate of 4°C / min;

[0130] (S3-2) The pre-carbonized felt obtained in S3-1 was carbonized in a tubular furnace at 1200°C for 3 h under a N2 atmosphere, with a heating rate of 5°C / min and a N2 flow rate of 5 mL / min;

[0131] (S3-3) The carbonized felt obtained in S3-2 was graphitized in a tubular furnace. In a N2 atmosphere, the temperature was first raised to 1000°C at a rate of 5°C / min and maintained for 1 h, and then raised to 2200°C at a rate of 5°C / min and maintained for 3 h. The ventilation rate of the protective gas was 350 m / s. 3 / h, to obtain the nitrogen-bismuth co-doped porous graphite felt.

[0132] Example 3

[0133] This embodiment provides a nitrogen-bismuth co-doped porous graphite felt, and the nitrogen-bismuth co-doped porous graphite felt is prepared by the following steps:

[0134] S1. Preparation of PAN-based carbon fiber soft felt:

[0135] The polyacrylonitrile-based carbon fibers with an average diameter of 8 μm and an average length of 70 mm were needle-punched at a density of 5 needles / cm 2 , obtain PAN-based carbon fiber soft felt; wherein the density of the PAN-based carbon fiber soft felt is 1.0 g / cm 3 , thickness is 4.5 mm.

[0136] S2. Jet spinning to prepare spinning substrate:

[0137] (S2-1) 12% polyacrylonitrile (number average molecular weight 10,000), 7% urea and 5% BiCl3 were dissolved in DMF under stirring (500 rpm), heated to 70 °C and stirred for 60 min to form a uniform precursor solution;

[0138] (S2-2) using a solution jet spinning process, injecting a precursor solution into a syringe, placing the PAN-based carbon fiber soft felt obtained in S1 on a receiving curtain, turning on a solution jet spinning device, spraying the precursor solution onto the PAN-based carbon fiber soft felt, collecting the spun fibers on the receiving curtain and drying them, and obtaining the spinning substrate;

[0139] The syringe advancement speed is 1 mL / min, the air pressure is 1 MPa, the distance between the spinneret and the receiving mesh curtain is 60 cm, the ambient temperature is 40°C, the humidity is 50%, and the spinning time is 8 h; the drying is to dry the material in a vacuum drying oven at 40°C for 8 h.

[0140] S3. Preparation of Nitrogen-Bi Co-doped Porous Graphite Felt:

[0141] (S3-1) The spinning substrate obtained in S2 was placed in a muffle furnace for pre-carbonization at 400°C for 3.5 h with a heating rate of 5°C / min;

[0142] (S3-2) The pre-carbonized felt obtained in S3-1 was carbonized in a tubular furnace at a temperature of 1500°C for 4 h under a N2 atmosphere, with a heating rate of 5°C / min and a N2 flow rate controlled at 5 mL / min;

[0143] (S3-3) The carbonized felt obtained in S3-2 was graphitized in a tubular furnace. In a N2 atmosphere, the temperature was first raised to 1200°C at a rate of 5°C / min and maintained for 1 h, and then raised to 2400°C at a rate of 5°C / min and maintained for 3 h. The ventilation rate of the protective gas was 500 m / s. 3 / h, to obtain the nitrogen-bismuth co-doped porous graphite felt.

[0144] Example 4

[0145] This embodiment provides a nitrogen-bismuth co-doped porous graphite felt, which differs from Embodiment 1 only in that, in S2-1, the precursor solution is composed of the following components in percentage by mass: 2% polyacrylonitrile, 1% urea, 10% bismuth salt, and the remainder is solvent; other settings are exactly the same as Embodiment 1.

[0146] Example 5

[0147] This embodiment provides a nitrogen-bismuth co-doped porous graphite felt, which differs from Embodiment 1 only in that, in S2-1, the precursor solution is composed of the following components in percentage by mass: 1% polyacrylonitrile, 11% urea, 1% bismuth salt, and the remainder is solvent; other settings are exactly the same as Embodiment 1.

[0148] Example 6

[0149] This embodiment provides a nitrogen-bismuth co-doped porous graphite felt, which is different from Example 1 only in that, during the jet spinning of the S2-2 solution, the syringe propulsion speed is 0.2 mL / min, the air pressure is 0.1 MPa, the distance between the spinneret and the receiving plate is 20 cm, and the spinning time is 12 h; the other settings are exactly the same as those in Example 1.

[0150] Example 7

[0151] This embodiment provides a nitrogen-bismuth co-doped porous graphite felt, which is different from Example 1 only in that, during the jet spinning of the S2-2 solution, the syringe propulsion speed is 3.2 mL / min, the air pressure is 1.5 MPa, the distance between the spinneret and the receiving plate is 80 cm, and the spinning time is 4 h; the other settings are exactly the same as those in Example 1.

[0152] Example 8

[0153] This embodiment provides a nitrogen-bismuth co-doped porous graphite felt, which is different from Embodiment 1 only in that, in the S3-1 pre-carbonization process, the pre-carbonization is performed at 180° C. for 4 h; other settings are exactly the same as Embodiment 1.

[0154] Example 9

[0155] This embodiment provides a nitrogen-bismuth co-doped porous graphite felt, which is different from Embodiment 1 only in that, in the S3-1 pre-carbonization process, the pre-carbonization is performed at 320° C. for 0.5 h; other settings are exactly the same as Embodiment 1.

[0156] Example 10

[0157] This embodiment provides a nitrogen-bismuth co-doped porous graphite felt, which is different from Embodiment 1 only in that, during the S3-2 carbonization process, the carbonization is performed at 750° C. for 4 h; other settings are completely consistent with Embodiment 1.

[0158] Embodiment 11

[0159] This embodiment provides a nitrogen-bismuth co-doped porous graphite felt, which is different from Embodiment 1 only in that, during the S3-2 carbonization process, the carbonization is performed at 1250° C. for 0.5 h; other settings are exactly the same as Embodiment 1.

[0160] Example 12

[0161] This embodiment provides a nitrogen-bismuth co-doped porous graphite felt, which is different from Embodiment 1 only in that, during the S3-3 graphitization process, the temperature is first increased to 1500°C at a rate of 1°C / min and maintained for 6 h, and then increased to 3200°C at a rate of 15°C / min and maintained for 4 h; other settings are exactly the same as Embodiment 1.

[0162] Example 13

[0163] This embodiment provides a nitrogen-bismuth co-doped porous graphite felt, which differs from Embodiment 1 only in that, during the S3-3 graphitization process, the temperature is first increased to 700°C at a rate of 15°C / min and maintained for 4 h, and then increased to 1800°C at a rate of 1°C / min and maintained for 6 h; other settings are exactly the same as Embodiment 1.

[0164] Comparative Example 1

[0165] This comparative example provides a graphite felt, which is different from Example 1 only in that in S1, the polyacrylonitrile-based carbon fiber is replaced by asphalt-based carbon fiber; other settings are exactly the same as Example 1.

[0166] Comparative Example 2

[0167] This comparative example provides a graphite felt, which is different from Example 1 only in that, in S2-1, polyacrylonitrile is no longer added to the precursor solution, and the urea content is increased to 11%; other settings are exactly the same as Example 1.

[0168] Comparative Example 3

[0169] This comparative example provides a graphite felt, which is different from Example 1 only in that, in S2-1, urea is no longer added to the precursor solution, and the polyacrylonitrile content is increased to 11%; other settings are exactly the same as Example 1.

[0170] Comparative Example 4

[0171] This comparative example provides a graphite felt, which differs from Example 1 only in that, in S2-1, BiCl3 is no longer added to the precursor solution, the polyacrylonitrile content is increased to 9%, and the urea content is increased to 4%; other settings are exactly the same as Example 1.

[0172] Comparative Example 5

[0173] This comparative example provides a graphite felt, which differs from Example 1 only in that, in S2-2, an electrospinning process is used instead of solution jet spinning; the parameters of the electrospinning are as follows: the syringe pushing speed is 2.0 mL / min, the positive pressure is 16 kV, the negative pressure is 5 kV, the distance between the needle and the receiver is 10 cm, the roller receiver speed is 2500 rpm, the ambient temperature is 30°C, the humidity is 30%, and the spinning time is 6 h; the other settings are exactly the same as those in Example 1.

[0174] Comparative Example 6

[0175] This comparative example provides a graphite felt, which differs from Example 1 only in that the pre-carbonization treatment of S3-1 is no longer performed, but the S3-2 carbonization treatment is directly performed; other settings are completely consistent with Example 1.

[0176] Comparative Example 7

[0177] This comparative example provides a graphite felt, which is different from Example 1 only in that, during the graphitization treatment process of S3-3, the temperature is directly increased to 2200°C at a heating rate of 10°C / min and maintained at 2200°C for 10 h; other settings are completely consistent with Example 1.

[0178] Test Example 1

[0179] Test samples: the nitrogen-bismuth co-doped porous graphite felt provided in Examples 1 to 13 and the graphite felt provided in Comparative Examples 1 to 7.

[0180] Test items: HER test was performed on the manufactured graphite felt electrode, and it was assembled on the battery stack for testing. The voltage efficiency, coulomb efficiency and energy efficiency were tested and recorded under the same test conditions.

[0181] The test results are shown in Table 1 below:

[0182] Table 1

[0183]

[0184] As shown in Table 1, after the nitrogen-bismuth co-doped porous active graphite felt provided by the present invention is used as an electrode, the current density at a potential of 0.2 V is 0.0212-0.0329 A / cm 2 , voltage efficiency is 69.0~85.6%, energy efficiency is 71.0~84.8%, and coulomb efficiency is 71.6~95.8%. Examples 1~3 are preferred embodiments of the present invention. After the provided nitrogen-bismuth co-doped porous active graphite felt is used as an electrode, the current density at a potential of 0.2V is 0.0212~0.0245 A / cm 2 , voltage efficiency is 77.3-85.6%, energy efficiency is 74.3-84.8%, and coulombic efficiency is 85.2-95.8%. It can be seen that the present invention has higher voltage efficiency and energy efficiency. The battery efficiency can be used to feedback that the porous graphite felt structure of the present invention can greatly increase the specific surface area of ​​the graphite felt, improve and enhance the hydrophilicity, increase the conductivity of the graphite felt, and increase the surface functional groups, which are beneficial to improving the efficiency of the vanadium liquid flow battery.

[0185] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing nitrogen-bismuth co-doped porous graphite felt for use as an electrode for an all-vanadium redox flow battery, characterized in that: The preparation method comprises the following steps: The polyacrylonitrile-based carbon fibers are needle-punched to obtain PAN-based carbon fiber soft felt; dissolving polyacrylonitrile, urea and bismuth salt in a solvent to obtain a precursor solution; The precursor solution is composed of the following components by mass percentage: 8-14% polyacrylonitrile, 3-10% urea, 2-8% bismuth salt, and the balance is solvent; the bismuth salt is selected from bismuth chloride and / or bismuth nitrate; placing the PAN-based carbon fiber felt on a receiving curtain, starting a solution jet spinning device to spray the precursor solution onto the PAN-based carbon fiber felt, collecting the spun substrate and drying it to obtain a spinning substrate; The parameters of the solution jet spinning process include the following conditions: the propulsion speed of the syringe is 0.3-3.0 mL / min, the air pressure is 0.2-1.0 MPa, the distance between the spinneret and the receiving plate is 30-70 cm; the ambient temperature is 20-40°C, the ambient humidity is 20-50%; the spinning time is 5-10 h; The spinning substrate is sequentially subjected to pre-carbonization, carbonization and graphitization to obtain the nitrogen-bismuth co-doped porous graphite felt; The temperature of the pre-carbonization treatment is 220-300°C, and the time of the pre-carbonization treatment is 1-3 hours; the temperature of the carbonization treatment is 800-1200°C, and the time of the carbonization treatment is 1-3 hours; the treatment procedure of the graphitization treatment is: first heating to 800-1200°C and maintaining for 0.5-10 hours, then heating to 2000-3000°C and maintaining for 0.5-10 hours.

2. The method for preparing nitrogen-bismuth co-doped porous graphite felt for use as an electrode for an all-vanadium redox flow battery according to claim 1, characterized in that: The average diameter of the polyacrylonitrile-based carbon fibers is 5-10 μm, and the average length is 50-100 mm; And / or, the density of the acupuncture treatment is 1 to 10 needles / cm 2 ; And / or, the density of the PAN-based carbon fiber soft felt is 0.6-1.0 g / cm 3 , thickness is 2~6 mm.

3. The method for preparing nitrogen-bismuth co-doped porous graphite felt for use as an electrode for an all-vanadium redox flow battery according to claim 1, characterized in that: The number average molecular weight of the polyacrylonitrile is 80,000 to 150,000; And / or, the solvent is selected from N,N -dimethylformamide; and / or, the dissolving temperature is 60-80° C.; And / or, the dissolution is carried out under stirring conditions, the stirring speed is 200-400 rpm, and the stirring time is 20-200 min.

4. The method for preparing nitrogen-bismuth co-doped porous graphite felt for use as an electrode for an all-vanadium redox flow battery according to claim 1, characterized in that: The drying temperature is 25-100° C., and the drying time is 1-4 h.

5. The method for preparing nitrogen-bismuth co-doped porous graphite felt for use as an electrode for an all-vanadium redox flow battery according to claim 1, characterized in that: The heating rate of the pre-carbonization treatment is 5°C / min or less.

6. The method for preparing nitrogen-bismuth co-doped porous graphite felt for use as an electrode for an all-vanadium redox flow battery according to claim 1, characterized in that: The carbonization treatment is carried out in the presence of a protective gas; and / or, the protective gas comprises nitrogen and / or argon; and / or, the flow rate of the protective gas is 5 mL / min or more; And / or, the heating rate of the carbonization treatment is below 5°C / min.

7. The method for preparing nitrogen-bismuth co-doped porous graphite felt for use as an electrode for an all-vanadium redox flow battery according to claim 1, characterized in that: The graphitization treatment is carried out in the presence of a protective gas; and / or, the protective gas comprises nitrogen and / or argon; And / or, the ventilation rate of the protective gas is 300-500 m 3 / h; And / or, the heating rate of the graphitization treatment is 5-10°C / min.

8. A nitrogen-bismuth co-doped porous graphite felt for use as an electrode for an all-vanadium redox flow battery, characterized in that: The nitrogen-bismuth co-doped porous graphite felt is prepared by the method for preparing the nitrogen-bismuth co-doped porous graphite felt used as an electrode of an all-vanadium redox flow battery as claimed in any one of claims 1 to 7.

9. Use of the nitrogen-bismuth co-doped porous graphite felt as claimed in claim 8 for use as an electrode for an all-vanadium redox flow battery in the preparation of an electrode for an all-vanadium redox flow battery.

Citation Information

Patent Citations

  • Monatomic catalyst composite electrode for all-vanadium redox flow battery as well as preparation and application of monatomic catalyst composite electrode

    CN116314856A

  • Preparation method for combination electrode for all-vanadium redox flow battery

    CN104241661A

  • Preparation method of carbon felt for redox flow battery

    CN115881981A

  • Nitrogen-doped oriented carbon fiber three-scale composite electrode and zinc-based flow battery thereof

    CN118507755A